Structural integrity of the ribonuclease H domain in HIV‐1 reverse transcriptase. Issue 8 (1st July 2015) - Slack, Ryan L.; Spiriti, Justin; Ahn, Jinwoo; Parniak, Michael A.; Zuckerman, Daniel M.; Ishima, Rieko
ABSTRACT The mature form of reverse transcriptase (RT) is a heterodimer comprising the intact 66‐kDa subunit (p66) and a smaller 51‐kDa subunit (p51) that is generated by removal of most of the RNase H (RNH) domain from a p66 subunit by proteolytic cleavage between residues 440 and 441. Viral infectivity is eliminated by mutations such as F440A and E438N in the proteolytic cleavage sequence, while normal processing and virus infectivity are restored by a compensatory mutation, T477A, that is located more than 10 Å away from the processing site. The molecular basis for this compensatory effect has remained unclear. We therefore investigated structural characteristics of RNH mutants using computational and experimental approaches. Our Nuclear Magnetic Resonance and Differential Scanning Fluorimetry results show that both F440A and E438N mutations disrupt RNH folding. Addition of the T477A mutation restores correct folding of the RNH domain despite the presence of the F440A or E438N mutations. Molecular dynamics simulations suggest that the T477A mutation affects the processing site by altering relative orientations of secondary structure elements. Predictions of sequence tolerance suggest that phenylalanine and tyrosine are structurally preferred at residues 440 and 441, respectively, which are the P1 and P1' substrate residues known to require bulky side chains for substrate specificity. Interestingly, our study demonstrates that the processing site residues, which are critical for protease substrate specificity and must be exposed to the solvent for efficient processing, also function to maintain proper RNH folding in the p66/p51 heterodimer. Proteins 2015; 83:1526–1538. © 2015 Wiley Periodicals, Inc.